A T-RFLP database for the rapid profiling of methanogenic communities in anaerobic digesters. (June 2016) - Bühligen, Franziska; Lucas, Rico; Nikolausz, Marcell; Kleinsteuber, Sabine
Abstract: We present a simple protocol for the cost- and time-efficient profiling of methanogens based on T-RFLP fingerprinting of mcrA amplicons. Sequence data were compiled from mesophilic lab-scale and full-scale biogas reactors operated under various conditions and fed with various substrates. The database facilitates the rapid identification of methanogens, thus reducing the need of cloning and sequencing. Highlights: A database for T-RFLP profiling of methanogens in anaerobic digesters is presented. T-RF values of mcrA amplicons can be assigned at least to the family level. Methanogens in biogas reactors can be identified without cloning and sequencing.